High Parental Vaccine Motivation at a Neighborhood-Based Vaccine and Testing Site Serving a Predominantly Latinx Community (Mary Ann Liebert, 2021)
Purpose: To understand vaccine attitudes of Latinx parents highly impacted by COVID-19. Methods: In April 2021, we surveyed parents about their attitudes for COVID-19 vaccination of their children at a community-based outdoor testing/vaccination site serving predominantly low-income Latinx persons in San Francisco. Results: Among 1033 parents (75% Latinx), 92% would ?definitely? or ?probably? vaccinate their children. Vaccine concerns were higher for younger children and included side effects and impacts on fertility. Doctors and community organizations were noted as trusted sources of information, including among vaccine-concerned parents. Conclusion: Latinx parents accessing neighborhood-based COVID-19 testing/vaccination services are highly motivated to vaccinate their children for COVID-19.